2012
DOI: 10.1029/2012gl051696
|View full text |Cite
|
Sign up to set email alerts
|

Interseismic seafloor crustal deformation immediately above the source region of anticipated megathrust earthquake along the Nankai Trough, Japan

Abstract: We monitored seafloor crustal deformation using the GPS/acoustic seafloor geodetic observation technique at three sites on the Kumano Basin, off southwestern Japan, which is located immediately above the source region of the anticipated Tonankai megathrust earthquake. We directly measured landward crustal movements of ∼40 mm/y in the ∼N80°W direction with respect to the Amurian Plate on the seafloor. The directions were found to be the same as those measured at the on‐land GPS stations. The magnitudes of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 31 publications
0
39
0
Order By: Relevance
“…Earthquakes are scattered mainly in the oceanic crust and uppermost mantle, and there are very few events along the plate boundary. Low seismicity at the plate boundary may reflect a strong coupling ratio (> 80%) between the plates in this region (e.g., Tadokoro et al, 2012;Yoshioka and Matsuoka, 2013). Northeast-southwest cross sections (almost parallel to the trough axis) show the seismicity separated into a southwestern and a northeastern cluster (Fig.…”
Section: Seismic Activity Along the Nankai Troughmentioning
confidence: 96%
“…Earthquakes are scattered mainly in the oceanic crust and uppermost mantle, and there are very few events along the plate boundary. Low seismicity at the plate boundary may reflect a strong coupling ratio (> 80%) between the plates in this region (e.g., Tadokoro et al, 2012;Yoshioka and Matsuoka, 2013). Northeast-southwest cross sections (almost parallel to the trough axis) show the seismicity separated into a southwestern and a northeastern cluster (Fig.…”
Section: Seismic Activity Along the Nankai Troughmentioning
confidence: 96%
“…The subducting seamount (Kodaira et al 2000) and the Paleo-Zenisu and deeper Paleo ridges Park et al 2003) are shown by light blue regions. The light blue and red arrows indicate the seafloor velocity vectors observed by Nagoya University (Tadokoro et al 2012) and the authors, respectively.…”
Section: Competing Interestsmentioning
confidence: 88%
“…Our past observations near the Japan Trench provided great advantage in understanding the 2005 Off-Miyagi Prefecture earthquake (M7.2) (e.g., Matsumoto et al 2006 andSato et al 2011b), the 2011 Tohoku-oki earthquake (M9.0) (e.g., Sato et al 2011a andSato et al 2013b), and others. Important observations have also been made by other research groups in Japan such as Tohoku University (e.g., Kido et al 2006 andKido et al 2011) and Nagoya University (e.g., Tadokoro et al 2012 andYasuda et al 2014).…”
Section: Seafloor Geodetic Observation Using a Gps-acoustic Combinatimentioning
confidence: 94%
See 1 more Smart Citation
“…In Japan, our group first succeeded in detecting seafloor movements caused by interseismic plate convergence at the Japan Trench ) and has continued to monitor the movements including coseismic and postseismic deformation at the seafloor sites along the Japan Trench (e.g., Matsumoto et al 2006;Sato et al 2011a, b;Sato et al 2013b;Watanabe et al 2014) and the Nankai Trough (e.g., Yokota et al 2015). Moreover, other groups in Japan have provided important results (Kido et al 2006;Kido et al 2011;Tadokoro et al 2012;Yasuda et al 2014) to understand the major interplate earthquakes as well. Figure 1 shows a schematic picture of the GPSacoustic positioning system developed by our group.…”
Section: Methods and Observation Datamentioning
confidence: 97%